GRAPHS OF EXACT SOLUTIONS OF ORDINARY DIFFERENTIAL EQUATIONS IN MAPLE - Nastinov Sadriddin Tojiddin o‘g‘li; Abdukodirov Elbek Abduvali ugli (Web of Journals Publishing, 2025)
This article analyzes the structure and structure of ordinary differential equations in the Maple system in a clear and sufficient manner. Compared to other systems, the solution and graph are clear and understandable.
Keywords: Restat, equation diff(y(x),x$2)+y(x)=x, >dsolve(differential,y(x)), plot(exact solution, x=a..b, color=blue). The LN system can also be solved using the >dsolve command. For this, it should be written in the form >dsolve({sys},{x(t),y(t),…}), a system of sys-ODTs, x(t),y(t) ,.. .-system of unknown functions.